Adaptation of the PESTonFARM Model to Support Decision-Making and Planning of Local Implementation of the Sterile Insect Technique in the Control of Ceratitis capitata Flies (Diptera: Tephritidae) - Slawomir Antoni Lux; Marco Colacci (Applied Sciences, 2025)
The Sterile Insect Technique (SIT) is most effective at large regional scales when applied within an area-wide framework. However, there is a need to investigate its feasibility at smaller scales, e.g., for emergency responses to local fruit fly invasions or planning for preventive release of sterile males in local high-risk zones. Available decision support tools and SIT implementation models are effective for large-scale interventions but tend to ignore the influences of fine-grained terrain structures and therefore offer little guidance for small-scale SIT operations in locally diverse landscapes. This study addresses this issue by adapting a site-specific individual-based PESTonFARM model to simulate both the behaviour and fate of individual members of ultra-small invasive medfly propagules and the post-release dispersal and mating performance of sterile males in heterogeneous and mosaic landscapes. To illustrate model operation, several SIT implementation scenarios were simulated to reveal the influence of local landscape structure on the behaviour of wild and released sterile males and to quantitatively assess the effectiveness of different SIT scenarios. Our results demonstrate the sensitivity of the model and showed that the influence of the spatiotemporal structure of local resources should not be ignored when planning local SIT operations.